Persepsi Ulama Kota Banjarmasin terhadap Hak-Hak Reproduksi Perempuan - Saifuddin, Saifuddin (IAIN Antasari Banjarmasin, 2015)
Many Islamic studies, recently, have emerged along with the rise of gender discourse andÂ women issues in many Islamic and public colleges in the country, including in Banjarmasin,Â South Kalimantan. One issue arising is that the womenâs reproductive rights in religiousÂ perspective seems to be underestimated. This view is of course influenced by the role of Muslimscholars as Muslims role models and mentors. Thus, it becomes significant to investigate theÂ perception of Muslim scholars on the womenâs reproductive rights in order to find out theirÂ insight and appreciation on womenâs rights. The conducted field study employs descriptiveÂ method and normative-sociological approach and it is found that the Muslim scholars haveÂ relatively the same level of appreciation. According to them, the womenâs reproduction rightswhich includes in the period of menstruation, pregnancy, childbirth, and raising children, isÂ a matter that must be considered and met by the men in the family. Some factors that haveÂ influenced the Muslim scholarsâ perception are devided in two dimensionsâframe of referenceÂ which includes education, reading sources, and results of study, and frame of experienceÂ which includes self-experience, and the surrounded cultural, political, and social environment